EVALUATING THE EFFECTIVENESS OF BLENDED LEARNING ON STUDENTS’ LEARNING OUTCOME IN INTERIOR DESIGN MATERIAL AND CONSTRUCTION COURSE - Jain, Ruchira; Datt, Sachin (ShodhKosh: Journal of Visual and Performing Arts, 2025)
Interior design materials courses are essential for preparing students for real-world professional practice. Students must not only understand the characteristics and appropriate applications of various materials but also think critically about material selection to meet both aesthetic and functional requirements. Blended learning—a combination of online instruction and face-to-face engagement—offers a promising approach by integrating self-directed digital resources with hands-on, interactive activities. This study investigates the impact of blended learning on student learning outcomes in a postgraduate interior design materials course, employing a quasi-experimental post-test-only design. One group of students participated in a blended learning model that combined online instruction with hands-on lab activities. A second group engaged in traditional classroom instruction paired with lab activities, while a third group followed a conventional lecture-based classroom format without lab engagement. Bloom’s Taxonomy was used as the framework for assessing learning outcomes, with post-test questions targeting all cognitive levels—from remembering and understanding to creating. Results indicated that students in the blended learning group outperformed their peers in higher-order cognitive skills, particularly in analyzing, evaluating, and creating practical material solutions. The findings also revealed no significant difference in lower-order thinking skills (e.g., remembering and understanding) between students taught through traditional classroom methods and those taught online.